INDEKS MASSA TUBUH DAN TINGKAT KEBUGARAN JASMANI PADA REMAJA USIA 13-15 TAHUN DI KECAMATAN RONGKOP KABUPATEN GUNUNG KIDUL DAN DI KOTA YOGYAKARTA - , SONIA PUTRI PRATAMANINGTYAS, Dra. Neni Trilusiana Rahmawati, M.Kes., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Introduction: Modernization and globalization made technology have developed greatly, these make adolescent live in instant way. It cause lack of physical activity that affecting body composition and physical fitness. Objective : To determine the correlation between Body Mass Index and Physical Fitness level and the differences of Body Mass Index and Physical Fitness level between boys and girls 13-15 years old. Method: This cross sectional study was conducted to 151 students aged 13-15 years old of SMP N 1 Rongkop and SMP 3 Yogyakarta from July to August 2012. Physical Fitness level tested using Harvard Step up Test. Anthropometric measurement was conducted to measure Body Mass Index. The correlation between Physical Fitness level and Body Mass Index were analyzed with Spearman correlation and the comparison of Body Mass Index and Physical Fitness level between boys and girls were analyzed with Mann Whitney. Prior to the analysis test, the normality of sample data was checked. Result: 151 participants are devided into two groups, Rongkop (34 boys and 49 girls) and Kota Yogyakarta group (34 boys and 34 girls). The result showed that there was no correlation between Body Mass Index and Physical Fitness level among boys (r=-0,122